2014
DOI: 10.1242/jcs.150227
|View full text |Cite
|
Sign up to set email alerts
|

GEF-H1 controls focal adhesion signaling that regulates mesenchymal stem cell lineage commitment

Abstract: Focal adhesions (FAs) undergo maturation that culminates in size and composition changes that modulate adhesion, cytoskeleton remodeling and differentiation. Although it is well recognized that stimuli for osteogenesis of mesenchymal stem cells (MSCs) drive FA maturation, actin organization and stress fiber polarization, the extent to which FA-mediated signals regulated by the FA protein composition specifies MSC commitment remains largely unknown. Here, we demonstrate that, upon dexamethasone (osteogenic indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 62 publications
2
24
0
Order By: Relevance
“…140,141 RhoA/ROCK pathway in MSCs can be also altered through the inhibition of GEF-H1, leading to the disruption of FAs, inhibition of osteogenesis, and stimulation of adipogenic commitment in bMSCs. 142 Activation of RhoA/ROCK, either by the tension increases or by GEF-H1 releases from the dynamic MTs, is favorable for osteogenesis and inhibits chondrogenic and adipogenic commitment of MSCs. 16,142 RAF/MEK/Erk is the second and the most underexplored signaling pathway that refers to the differentiation of MSCs.…”
Section: Signaling Pathways and Their Cross-talk In Msc Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…140,141 RhoA/ROCK pathway in MSCs can be also altered through the inhibition of GEF-H1, leading to the disruption of FAs, inhibition of osteogenesis, and stimulation of adipogenic commitment in bMSCs. 142 Activation of RhoA/ROCK, either by the tension increases or by GEF-H1 releases from the dynamic MTs, is favorable for osteogenesis and inhibits chondrogenic and adipogenic commitment of MSCs. 16,142 RAF/MEK/Erk is the second and the most underexplored signaling pathway that refers to the differentiation of MSCs.…”
Section: Signaling Pathways and Their Cross-talk In Msc Differentiationmentioning
confidence: 99%
“…142 Activation of RhoA/ROCK, either by the tension increases or by GEF-H1 releases from the dynamic MTs, is favorable for osteogenesis and inhibits chondrogenic and adipogenic commitment of MSCs. 16,142 RAF/MEK/Erk is the second and the most underexplored signaling pathway that refers to the differentiation of MSCs. The complied map of this network consists of more than 250 components and 440 links.…”
Section: Signaling Pathways and Their Cross-talk In Msc Differentiationmentioning
confidence: 99%
“…These methods relied on stabilisation of IACs using chemical cross-linkers and enrichment of IAC components by removal of the cell body and cytoplasmic proteins (Jones et al, 2015; Kuo et al, 2012). Mass spectrometry was then used to determine IAC compositions for several cell types under a variety of culture conditions (Ajeian et al, 2016; Byron et al, 2012, 2015; Horton et al, 2015, 2016a; Huang et al, 2014; Humphries et al, 2009; Kuo et al, 2011; Ng et al, 2014; Robertson et al, 2015; Salmela et al, 2016; Schiller et al, 2011, 2013; Yue et al, 2014). Seven of these mass spectrometry datasets, which were generated from different laboratories using diverse methods and from multiple cell types, were used to create a ‘meta-adhesome’ database of more than 2000 proteins that were enriched at fibronectin-induced IACs (Horton et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…To provide global insights into IAC biology, recent studies have isolated IACs biochemically and analyzed their molecular composition using mass spectrometry (MS)–based proteomics ( Kuo et al, 2012 ; Jones et al, 2015 ). These studies have revealed an unanticipated complexity in IAC composition in different contexts ( Humphries et al, 2009 ; Kuo et al, 2011 ; Schiller et al, 2011 , 2013 ; Byron et al, 2012 , 2015 ; Huang et al, 2014 ; Ng et al, 2014 ; Yue et al, 2014 ; Ajeian et al, 2015 ; Robertson et al, 2015 ; Horton et al, 2015a ). In particular, analysis of the effects of myosin-II inhibition on IAC composition revealed the force-sensitive nature of LIN-11, Isl1, and MEC-3 domain–containing IAC components ( Kuo et al, 2011 ; Schiller et al, 2011 ; Horton et al, 2015a , b ).…”
Section: Introductionmentioning
confidence: 99%